Photocatalytic Oxidative Dehydrogenation of Ethane Using CO2 as a Soft Oxidant over Pd/TiO2 Catalysts to C2H4 and Syngas - Zhang, Ronghao; Wang, Hong; Tang, Siyang; Liu, Changjun; Dong, Fan; Yue, Hairong; Liang, Bin (ACS catalysis, 2018)
Using CO2 as the soft oxidant for the oxidative dehydrogenation of ethane (ODE) is a potential advancement for ethylene production from ethane. However, the current ODE reaction is primarily operated at high temperatures (e.g., 873 K), and the development of alternative approaches for the ODE reaction under the mild conditions is still a challenge. Herein, we report a photocatalytic ODE using CO2 as the oxidant over Pd/TiO2 catalysts at room temperature. The presence of CO2 significantly promoted the production of C2H4 and syngas, and the 1% Pd/TiO2 catalyst exhibited a C2H4 production rate of 230.5 μmol/gcat·h and syngas of 282.6 μmol/gcat·h. Density functional theory (DFT) calculation verified that the intermediate energy level provided by Pd and the covalent bond in Pd–O stimulated the electron transfer, excitation, and separation. The photoinduced electron, hole, and isolate OH on the surface of TiO2 played essential roles during the whole process. In addition, the possible reaction pathways of photocatalytic ODE with CO2 were proposed on the basis of the experimental data and DFT calculation results.